Ovarian small cell carcinoma of pulmonary type appearing in ante-mortem ascites: An autopsy case and review of the literature - Hirotsugu Hashimoto, MD; Atsushi Kurata, MD, PhD; Koji Fujita, CT; Hideto Shimada, MD; Takeshi Nagai, MD; Hajime Horiuchi, MD; Masahiko Kuroda, MD, PhD (Elsevier, 2015)
Ovarian small cell carcinoma of pulmonary type (OSCCPT) is an extremely rare and aggressive disease. The diagnostic significance of cytology of ascites for OSCCPT, however, has not been shown so far. Here, we report the diagnosis of this carcinoma in an autopsy case with ante-mortem cytology of ascites. A 75 year-old woman was detected with bilateral ovarian cancer by radiological imaging. Although operation was planned, massive ascites was discovered a few weeks later. Ascites was removed with abdominocentesis, which cytologically diagnosed presence of carcinoma, suspicious of adenocarcinoma. A few days later, she died. From autopsy samples, we diagnosed this case as bilateral OSCCPT, showing neuroendocrine differentiation by immunohistochemistry. We reviewed ante-mortem cytology of ascites and found scattered small atypical cells. Immunocytochemical study of the cell block of the ascites showed neuroendocrine differentiation of the atypical cells in an identical manner as the autopsy specimens. Since small atypical cells of OSCCPT often exist with other histological tumor components, careful screening of all cells on the preparation is advisable to accurately diagnose OSCCPT by cytology of ascites.